Role of Supply Chain Management in Indian Textile Industry and the key issues faced by the Textile Supply Chain - V, Prabavathi; R, Vanathi (Journal of Contemporary Research in Management (JCRM), 2019)
Supply chain management (SCM) is a crucial part of modern textiles and apparel business. In addition to the traditional concepts on improving the production efficiency, quality control, and product design, supply chain management focuses on enhancing the collaboration and cooperation among all companies in supply chain with a goal of satisfying what market wants. With the advance of technologies, both in terms of computer-based information technology and materials-science related production technology, many timely research issues emerge in supply chain management of textiles and apparels. The Indian textile industry needs efficient supply chain management. One area that needs more emphasis for global competitiveness of the entire supply chain is the interface between textiles and clothing. To keep all the systems in textile industry in order, it is ideal to have a proper supply chain management. Supply chain management has become an integral part of business in textiles. The role of supply chain management in textile industry, contribution of Indian textile industry towards the growth of the nation economy and the key issues faced and the strategy to be adopted by the supply chains in Indian textile industry is focused in this article.